Strategies to enhance the adaptation of learner nurses regarding midwifery experiential learning in clinical settings of Limpopo Province - Maaka, Seshwatlha Salome (My University, 2017)
BACKGROUND Midwifery learning encompasses both theory and experiential components. Experiential learning plays an important role in midwifery training. Conducting the first normal vaginal delivery seemed traumatic for the learner nurses when they witness the bulging of the perineum when the head of the fetus is crowning. The trauma and stress of learner nurses resulted in negative reactions such as fainting, vomiting, and failing midwifery experiential assessments. The aim of the study was to design the strategies to enhance the adaptation of learner nurses regarding midwifery experiential learning in the clinical settings of Limpopo Province. RESEARCH METHOD A quantitative descriptive cross-sectional research method was used to collect numeric data with regard to the factors that hinder the adaptation of learner nurses regarding midwifery experiential learning in the clinical settings of Limpopo province. Data was collected using a self-administered questionnaire and analysed using the Statistical Package for Social Sciences (SPSS) version 23 with the assistance of the statistician. RESULTS The study revealed that the factors that hinder the adaptation of learner nurses regarding midwifery experiential learning are lack of accompaniment of learner nurses to the maternity units, the anxiety experienced by learner nurses when they witnessed the first delivery, learner nurses not being included in decision making processes in the maternity units and the hostile attitudes of registered midwives towards the learner nurses in the maternity units. Strategies were developed to enhance the adaptation of learner nurses regarding midwifery experiential learning in the clinical settings of Limpopo province. CONCLUSION The study concluded that learner nurses faced challenges that hinder their adaptation to midwifery experiential learning in the clinical settings of Limpopo Province.
Thesis (M. Cur.) -- University of Limpopo, 2017
Keywords: Experiential learning; Midwifery; Learner nurses; Midwifery; Nursing students; Obstetrics